2005
DOI: 10.1080/09513590500099065
|View full text |Cite
|
Sign up to set email alerts
|

Yolk sac tumor in a young girl: A case report

Abstract: This is an interesting case of yolk sac tumor in a young girl, at an age typical for germ cell tumor. AFP represents a valid marker resulting in a useful diagnostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 4 publications
0
14
0
2
Order By: Relevance
“…Of all the genital tumors, yolk sac tumors are relatively uncommon and they are mostly discovered in infants and adolescents (median age, 19 years) (3). Although they typically arise from the gonads, YSTs have already been reported in many extragonadal sites.…”
Section: Discussionmentioning
confidence: 99%
“…Of all the genital tumors, yolk sac tumors are relatively uncommon and they are mostly discovered in infants and adolescents (median age, 19 years) (3). Although they typically arise from the gonads, YSTs have already been reported in many extragonadal sites.…”
Section: Discussionmentioning
confidence: 99%
“…Razi et al reported a case of ovarian yolk sac tumor with a markedly elevated serum AFP level of 1156 ng/mL. 9 Case report by Eddaoulline et al also showed an increase in the patient's serum AFP level to 52,330 ng/mL.5 Serum AFP level in yolk sac tumors will increase far beyond the normal value (<10 ng/mL), which is >1000 ng/ml. Alpha-fetoprotein is normally produced by the yolk sac during embryonic development, so a severe proliferation of yolk sac tumor cells will cause an increase in serum AFP levels in almost all cases.…”
Section: Discussionmentioning
confidence: 98%
“…Primary yolk sac tumor (YST) of the endometrium is very rare, and only 15 cases have been reported (1,2). This case report is the 16th case in the world.…”
Section: Introductionmentioning
confidence: 92%